Design of a new MISO mixed-mode universal biquad OTA-C filter in 130nm CMOS technology - Popadic, Goran (Informacije MIDEM, 2025)
This paper presents the design of a MISO (multiple-input single-output) universal biquad filter in 130 nm CMOS UMC technology. The proposed filter consists of three operational transconductance amplifiers (OTAs), two grounded capacitors and one inverter stage. The topology, which has three inputs and one output, operates in all modes: voltage, transconductance, current, and transresistance. In addition, the filter generates all types of transfer functions (LP, HP, BP, BS, and AP). First, the filter topology with an inverter at the output is designed and analyzed in detail. Next, an improved topology with a differential amplifier as the output stage is proposed. The designed filter has a cutoff frequency of approximately 250 MHz and a current consumption of 4.5 mA. The impact of process, temperature, and voltage variations is examined through corner analysis.
Keywords: analog IC design; filter OTA-C; MISO; operacijski transkonduktančni ojačevalnik; operational transconductance amplifier; OTA-C filter; universal biquad filter; univerzalni biquad filter; zasnova analognih integriranih vezij